Transcranial alternating current stimulation combined with sound stimulation improves the cognitive function of patients with Alzheimer's disease: A case report and literature review - Liu, Yang; Tang, Can; Wei, Kailun; Liu, Di; Tang, Keke; Chen, Meilian; Xia, Xuewei; Mao, Zhiqi (Frontiers in Neurology, 2022)
Transcranial alternating current stimulation (tACS) is a relatively new non-invasive brain electrical stimulation method for patients with Alzheimer (AD) but has poor offline effects. Therefore, we applied a new combined stimulation method. To observe the offline effect on cognitive function of AD patients. Here, we describe the clinical results of a case in which tACS combined with sound stimulation was applied to treat moderate AD. The patient was female, aged 73 years, with a 2-year history of persistent cognitive deterioration despite the administration of Aricept and Sodium Oligomannate. Therefore, tACS combined with sound stimulation was administered to this patient. Her cognitive scale scores improved after 15 sessions and continued to improve at the 4-month follow-up. Our current report may provide a new alternative therapy for AD patients, but more clinical data are needed to support its efficacy.